Introduction to robotics : analysis, control, applications / Saeed B Niku - Niku, Saeed B.
This new 3rd edition of the Introduction to Robotics textbook is the culmination of over a year of intense work. If judging the previous edition by the number of instructors who adopted it, number of countries in which it was popularly sold, and the number of language into which it was translated indicates that it was a good book, I hope that this new edition is even better. It has two completely new chapters on screw-based mechanics and on parallel robots, it has many new examples and homework problems, it has many new subjects in most chapters, and the writing has been edited and streamlined throughout